KEMEROSOTAN MORAL SISWA PADA MASA PANDEMIC COVID-19 : MENEROPONG EKSISTENSI GURU PENDIDIKAN AGAMA ISLAM - Gustav Gisela Nuwa (IAIN Bone, 2020)
Teachers have a very big share of the success of learning in schools on the development of their students both in terms of cognitive, affective and psychomotor. The purpose of this study was to determine how the moral decline of students during the Covid-19 pandemic: observing the role of Islamic religious education teachers. This research uses a descriptive qualitative approach. The results showed that, the role of Islamic Religious Education Teachers during the Covid-19 pandemic, namely: as a source of hope, as an agent of change, as an evaluator. The obstacles to learning Islamic religious education during the Covid-19 period were that most areas where students lived did not have 4G network access, parents' understanding of online learning was still very minimal, did not have an Android cellphone, and there was no data.